The distributional origins of the Canada-US GDP and labour productivity gaps - James MacGee; Joel Rodrigue (Bank of Canada, 2024)
Gross domestic product (GDP) per adult in Canada fluctuated between 70% and 90% of that of the United States between 1960 and 2020. Behind this gap lie large, systematic differences in relative incomes across the Canadian and US income distributions. There are small differences in average incomes among lower percentiles of the income distribution while large gaps exist for high-income earners, with larger gaps for business owners and the university-educated. Using data from the World Inequality Database, we find that the top 10% of the income distribution accounts for three-quarters of the gap in GDP per adult between Canada and the United States and up to two-thirds of the measured labour productivity gap. While average hours worked per working-age adult in Canada and the United States were similar in 1970 and 2019, persistent shifts in relative hours worked per adult appear to play a significant role in measured labour productivity differences between 1970 and 2019. Our work suggests that selective emigration of high-ability workers - commonly referred to as brain drain - to the United States may play a significant role in accounting for the gaps in GDP per adult and labour productivity. The lower level of innovative activities in Canada is consistent with larger income gaps for high-income earners.
Keywords: D31; E24; J24; J61; N12; O47; O51; 330; Productivity